2009
DOI: 10.1128/iai.00518-09
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion of Candida albicans to Endothelial Cells under Physiological Conditions of Flow

Abstract: Candida albicans is a commensal organism that under certain circumstances can become pathogenic. During systemic infection C. albicans is disseminated via the circulation to distant organs, where it causes multiple organ failure. Despite the severity of systemic C. albicans infection, little is known about the mechanisms involved in the adhesion of this organism to the endothelium lining blood vessels. Previous studies have used static assays to examine adhesion. However, these do not realistically model blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
61
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(67 citation statements)
references
References 26 publications
6
61
0
Order By: Relevance
“…In our model, inoculated yeast cells always adhered relatively poorly. This is in agreement with the results of Grubb et al (14), who found that yeast adhesion at pressures over 3 dynes/cm 2 was also low. Strikingly, we observed a dramatic increase in adhesion kinetics during the first hour of circulation.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…In our model, inoculated yeast cells always adhered relatively poorly. This is in agreement with the results of Grubb et al (14), who found that yeast adhesion at pressures over 3 dynes/cm 2 was also low. Strikingly, we observed a dramatic increase in adhesion kinetics during the first hour of circulation.…”
Section: Resultssupporting
confidence: 93%
“…Furthermore, we have used a pressure which is similar to that found in capillary networks, have quantified the orien-tation of fungal hyphae relative to flow, and have analyzed the importance of fungal viability, the role of serum factors, and the importance of hypha-associated genes by using mutants lacking regulators of morphogenesis. Similar to Grubb et al (14), we found that C. albicans yeast and hyphae can rapidly adhere under flow. However, we also found that an adaptation event associated with the yeast-to-hypha transition can greatly enhance C. albicans-endothelium adhesion during circulation.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…In addition, it has been shown that physical properties and an optimal length (neither too short nor too long) promote endothelial adhesion during flow conditions, similar to the conditions in the bloodstream [50]. Differences in hyphal length may also explain why, in contrast to our results with germ tubes, Grubb et al found yeast cells adhered better than hyphae [51]. Furthermore, it should be noted that yeast cells dispersed from biofilms display increased adherence compared with their planktonic counterparts [22].…”
Section: Albicans Escape From the Bloodstreammentioning
confidence: 48%
“…C. albicans hyphae bind to endothelium much more efficiently than do yeast forms (12) in static adhesion assays. However, under conditions of fluid flow, which may be more appropriate to simulate actual adhesion in the bloodstream, C. albicans yeast forms bound more efficiently to endothelium (13). Several C. albicans adhesins have been identified, including the Als (agglutinin-like sequence) family (14)(15)(16).…”
mentioning
confidence: 99%